The Profile of State Islamic Primary School Teacher Education in Palangka Raya - Rahmad Rahmad (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Teacher is a professional position or profession. As a teacher, one of the competencies needed is professional competence. This study aims to look at the profile or educational background of MI teachers in the city of Palangka Raya. This research is important for the PGMI Study Program because it is the initial data for mapping the educational background of teachers in MIN Palangka Raya so that it can be the initial basis for collaboration between the Ministry of Religion of Central Kalimantan Province and PGMI Study Program related to increasing qualifications or procurement of educators in MIN Palangka Raya. This study uses a qualitative approach with data collection techniques through interviews with the head of the state Islamic madrasah in Palangka Raya. The results obtained are that the latest education is appropriate with the work as a class teacher obtained a percentage of 36.36% of class teachers with educational backgrounds or the latest bachelor's degree in Islamic primary school or elementary school teacher education.